Studies in the ontology of Reinhardt Grossmann - Cumpa, Javier (Eide ;, 2010)
Reinhardt Grossmann is one of the most sophisticated, knowledgeable and original contemporary metaphysicians. Although he was a student of Bergmann, he influenced the development of Bergmann's metaphysics considerably. No philosopher other than Grossmann defends perception to that degree against the persistent skeptical arguments. He characterizes his epistemological positions as radical empiricism and radical realism. By realism Grossmann mainly means the view that the material things we perceive exist. It is thus also an ontological position and closely related to his empiricism. Grossmann's.